PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PENGGUNAAN JASA BENGKEL PT. ASTRA INTERNATIONAL TBK-DAIHATSU MAJAPAHIT SEMARANG - Trisnowati, Dalila Komala; Nugraha, Hari Susanta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2016)
The phenomenon of many workshops that have sprung up in Semarang who demanded the owner or manager of a workshop to create a strategy in order to compete other workshops competitors. This research uses 100 respondents. The sampling technique of this research is accidental sampling and the sampled population representative are customers of Astra Daihatsu Workshop Majapahit Semarang. The analysis of the data used is the correlation coefficient, determination coefficient, simple linear regression, multiple linear regression, t test, and F test. Based on the results of analysis show that partially the price variable contributing influence on decision service usage by 29,2%, the variable quality of service contribute to the decision influences the use of services by 68,3%. Simultaneously the price and quality of service contribute to the decision of services usage by 68.6%. The conclusion of this study case indicate that the price and quality of service partially and simultaneously influence the decision to use authorized services in PT. Astra International Tbk - Daihatsu Workshop Majapahit. Based on these results, Astra Daihatsu Workshop Majapahit Semarang already have right pricing and should be able to maintain good service quality, and need to continued research by the company and other parties to determine the effect of other variables.